Peranan Bahan Organik dan Pupuk Majemuk NPK dalam Menentukan Percepatan Pertumbuhan Tanaman Jagung (Zea mays Saccharata L.) pada Tanah Inceptisol (Suatu Kajian Analisis Pertumbuhan Tanaman) - Fabians J.D. Hitijahubessy; Adelina Siregar (Universitas Pattimura, 2016)
Agricultural management is currently facing the adverse effects of inorganic fertilizers; thus, the use of organic fertilizers should be encouraged, one of which is the use of compost. Organic fertilizers are fertilizers that are mostly or wholly composed of organic materials derived from plants and/or animals through decomposition process. It can be in solid or liquid form used to supply plant nutrients, improve physical, chemical and biological properties of the soil to accelerate the plant growth. On the other hand, the inorganic fertilizer is still used, although only as a basic fertilizer, while the combination of both organic and NPK inorganic fertilizer as a balanced treatment can generate the best growth and development of the plant. The aims of this research were to: 1) determine the best dose of compost and NPK compound fertilizer for vegetative growth of sweet corn; and 2) determine the dose of compost to determine the best plant biomass filling for sweet corn plant growth. This research was conducted in the greenhouse of Faculty of Agriculture Pattimura University, Ambon using two factors in factorial design in Complete Randomized Design, with three replications where the first factor was compost as K (without compost, 10 tons/ha, 20 tons/ha and 30 tons/ha) and the second factor is NPK compound fertilizer as P (without NPK compound fertilizer, 50 kg/ha and 100 kg/ha), so there were 36 experimental units. Against the observed variables of plant height, number of leaves and stem diameters measured every week for an interval of five weeks, the design of Split in Time using PROC GLM SAS 14 was used, while for the variables fresh and dry weight of plant (roots and above ground) PROC GLM SAS 14 was used. If there was a significant effect of the compost and NPK fertilizer treatment on the soil and plant observation variables, it was followed by Duncan multiple range (DMRT) test using PROC GLM SAS 14, Step wise analysis and orthogonal polynomial regression for composting factor and the best compound fertilizer in this experiment using MINITAB 17. The results showed that compost and NPK compound were able to accelerate the growth rate of corn plant, and the best time occurred in the fourth week after planting, where compost with dose 20-30 tons/ha combined with NPK compound 50-100 kg/Ha showed the best results for vegetative growth of corn plant.